LIQUEFACTION POTENTIAL ANALYSIS IN TRANS-SULAWESI RAILWAY, POLEWALI MANDAR-MAJENE SEGMENT USING CONE PENETRATION TEST METHOD - Zhafira, Dzikra; Sadisun, Imam Achmad (Bulletin of Geology, 2022)
Trans-Sulawesi Railway is the first railway in Sulawesi. One of the segments that is passed by this railway is Polewali Mandar-Majene segment, West Sulawesi. The research focused on this segment and mostly contains of Quaternary sediments such as alluvial. Liquefaction may occur because of earthquake that causes loss of strength within soils. Most of the cases, liquefaction occur in Quaternary sediments that are decomposed, loose, and unconsolidated. So, liquefaction analysis is needed on the research area to determine the liquefaction potential that might happen there. Liquefaction potential analysis was carried out using Cone Penetration Test method (CPT). The analysis was carried out by calculating liquefaction safety factor (FSL) and liquefaction potential index (LPI) at 14 CPT sites with varying depth from 3.8 meters – 14 meters. Based on the analysis, the liquefaction safety factor (FSL) value shown that the 14 CPT sites has a potential for liquefaction with Mw 7.5 earthquake because the FSL values are less than 1. Based on the calculation of LPI, the research area is in the high – highest category. Keywords: Cone Penetration Test (CPT), Polewali Mandar, liquefaction, Liquefaction Potential Index (LPI)